Defective Phagocytic Properties of HIV-Infected Macrophages: How Might They Be Implicated in the Development of Invasive Salmonella Typhimurium? - Lê-Bury, Gabrielle; Niedergang, Florence (Frontiers in Immunology, 2018)
Human immunodeficiency virus type 1 (HIV-1) infects and kills T cells, profoundly damaging the host-specific immune response. The virus also integrates into memory T cells and long-lived macrophages, establishing chronic infections. HIV-1 infection impairs the functions of macrophages both in vivo and in vitro, which contributes to the development of opportunistic diseases. Non-typhoidal Salmonella enterica serovar Typhimurium has been identified as the most common cause of bacterial bloodstream infections in HIV-infected adults. In this review, we report how the functions of macrophages are impaired post HIV infection; introduce what makes invasive Salmonella Typhimurium specific for its pathogenesis; and finally, we discuss why these bacteria may be particularly adapted to the HIV-infected host.